PENGARUH LINGKUNGAN KELUARGA DAN MOTIVASI BELAJAR TERHADAP PRESTASI AKADEMIK SISWA SEKOLAH DASAR - Jalaluddin; Sri Supiyati; Shahibul Ahyan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
International assessments such as PISA 2022, TIMSS 2019, and AKM 2022 highlight the crucial role of the family environment including parental education, the home learning atmosphere, and emotional support in shaping students’ academic achievement. Nevertheless, the situation in Elementary Schools of Cluster IV, Keruak District, reveals that approximately 40% of students still perform below the minimum passing standard, particularly in mathematics and the Indonesian language. This condition is largely attributed to insufficient family support, low motivation, limited learning facilities, and economic constraints. The present study seeks to examine the influence of the family environment and learning motivation on elementary school students’ academic achievement, both individually and simultaneously. A quantitative approach with an ex post facto design was employed, involving 120 fifth-grade students from Cluster IV Elementary Schools selected through proportional random sampling. The independent variables were the family environment (X₁) and learning motivation (X₂), while the dependent variable, academic achievement (Y), was assessed using students’ report card scores. Data were collected through a validated and reliable questionnaire (Cronbach’s Alpha > 0.90) and analyzed using multiple linear regression with SPSS Version 25 for Windows. Findings indicate that both the family environment and learning motivation exert a positive and significant effect on academic achievement. Collectively, these variables account for 42.8% of the variance in students’ achievement. The study underscores that family support, school context, and student motivation are essential determinants of academic success at the elementary level.